LEXICAL ANALYSIS OF THE VERB COOK AND LEARNING VOCABULARY: A CORPUS STUDY - Priyono Priyono (TEFLIN Journal: A publication on the teaching and learning of English, 2011)
English verbs have built-in properties that determine how they behave syntactically and generate appropriate meaning associated. With these inherent properties some verbs can fill in only in certain syntactic structures and some in others. The observation of the verb COOK using English corpus has revealed its lexical properties covering the area of syntax, semantics, and collocation suggesting uniqueness of its behaviours that are distinguishable from other verbs. Having found the lexical properties of COOK, this article concludes that the acquisition of lexicon should include lexical properties that reflect their level of competence. It also argues that the acquisition of lexical properties should be implicit, not through meta-linguistic knowledge. This would render early grammar teaching unnecessary. The acquisition of lexical properties should take place through subconscious process, not explicit grammar instruction. Many of these are grammatical aspects such as word order, sentence construction, grammatical and lexical collocations.